Delaware Inland Bays and Market Oyster (Crassostrea virginica) Quality for Consumption - Gulnihal Ozbay; Lathadevi Karuna Chintapenta; Talaysha Lingham; Stephen Lumor; Jung-lim Lee; Bettina Taylor; Shobha Sriharan; Samuel Besong (Journal of Food Quality)
Consumption of raw oysters is known to cause serious health conditions due to bioaccumulation of contaminants. As filter feeders, oysters ingest bacteria along with phytoplankton from their surrounding habitats. Ensuring seafood safety for human consumption is always a concern. Since oysters are consumed raw, disease causing organisms, environmental contaminants, toxins, chemicals, and even physical hazards such as soils and metals retained in the oysters can enter through feeding. The objective of this study was to determine the quality of oysters collected from Delaware Inland Bays (DIB) and compare them with market oysters. Environmental parameters were monitored from local waters of DIB classified as closed versus open for shellfish harvesting. Total aerobic bacteria and vibrio were higher in market oysters during the warmer months, with open water having the least microbial loads. There were no significant differences in total vibrio counts between the study sites (p=0.396), but significant differences were recorded over time (p=0.004). Water temperature and turbidity were directly proportional to total vibrio in oysters, and salinity was inversely related. Research findings in this study may help bring awareness of changes in bacterial loads due to seasonal changes and additional handling and storage.